Experiences of mental health nursing staff at occupational stressors in a service provider institution in Cali, Colombia - Ruíz, Ana María; Tovar, Jenniffer Andrea; Andrade, Verónica (Universidad y Salud, 2017)
Introduction: Nursing staff, who attend psychiatric patients, are confronted with differentiated occupational stressors. Objective: Interpret the experiences of mental health nursing staff when facing occupational stressors, ranging from three transactional cut stress models and Goffman paper theory. Materials and methods: A qualitative and phenomenological study was conducted. Semi-structured interviews were carried out with nurses from a health care institution. The analysis of content and map of the association of ideas was employed for the analysis. Results: The main occupational stressors found were: unfavorable physical resources and absence of others, patient characteristics, labor overload, interpersonal conflicts, lack of preparation and unpunctuality in salary. As a result, changes in the mental health of the staff and the provision of the services provided were found. Conclusions: The way in which the system of work is configured in the institution presents occupational stressors that affect all the participants, who confront them through their personal capacities, the available resources, the networks of support and the experience acquired; all this is permeated by the ways in which they understand and interpret their role in the framework of work.